Інформаційно-комунікаційні технології в епоху становлення смарт-промисловості: проблеми визначення та умови розвитку - Garkushenko, Oksana N. (Institute of Industrial Economics of NAS of Ukraine, 2018)
Approximately from 2010-2011 in the advanced economies of the world (from the standpoint of economic and technological development) there is a discussion on the need of transition to a new technological mode, known as "Industry 4.0" or "smart industry". This new mode implies a shift to consumer-oriented production based on cyberphysical systems, the widespread use of the Internet of things, the Industrial Internet of Things and Information and Communication Technologies (ICT).The above terms are relatively new, their interrelation and interdependence in different sources have different meaning, which makes it difficult to conduct an analysis of these phenomena, their cross-country comparison and perception by economic agents. This could adversely affect the development of state concepts and programs, aimed at transferring the country's economy to a new technological mode.Given this ambiguity in the interpretation of terminology, an in-depth study of ICT essence at the present stage of their development, their relationship with Internet of Things, Industrial Internet of Things, cyberphysical systems, as well as conditions, under which ICT development in countries of the world is stimulated, was conducted. For its disclosure, the paper uses etymological and semantic analysis, the method of comparison, elements of the historical approach in defining the essence of ICT concepts, the ICT sector, the ICT infrastructure, synthesis, induction and deduction methods in identifying conditions, conducive to the further development of ICT.As a result of the study, an author's definition of the term "ICT" was offered, the concepts of ICT sector and ICT infrastructure were refined. It was found that ICT alone does not solve economic and social problems, but can be a highly effective tool for mitigating them in the presence of a developed ICT infrastructure and a sustained economic and political situation in the country.Also the paper briefly describes the state of ICT in Ukraine in comparison with the leading countries in this sector and suggests some general recommendations for improving the situation.